Model Pembelajaran Kooperatif TGT Untuk Meningkatkan Hasil Belajar Passing Kaki Bagian Dalam Pada Permainan Sepak Bola - Candra, Candra Mauliya Hanafi; Kurniawan, Wing Prasetya; Weda, Weda; Putra, Rendhitya Prima (YLPK Mahardhika, 2024)
The aim of this research is to improve the learning outcomes of inside foot passing in soccer games through the Teams Games Tournament (TGT) model. The method used is classroom action research. The subjects of this research were all 35 students at MI Al Hidayah. The sequence of this research includes: 1. Planning, 2. Implementation, 3. Observation, 4. Reflection. Data collection uses lesson plans, observation sheets and documentation. Data analysis uses percentage descriptions. The research results show that in cycle 1 the average inside leg passing skill was 59, 5 students or 14% got a score above 75 (KKM). Meanwhile, in cycle 2 the average inside foot passing skill was 81%, there were 27 students who got a score above 75 (KKM) or 77%. The results of this research can conclude that applying the affective teams games tournament (TGT) learning model can improve learning outcomes for inside-leg passing in MI Al Hidayah students.